Numerical Investigation of Boiling Flow in Oval Tube with Different Ellipticity - Liaw, K.L. (Institute of Physics, 2022)
Improving heat transfer has been the continuous quest in thermal engineering field. With higher transfer rate required, many researchers have shifted their attention towards boiling heat transfer that offer superior transfer rate. Despite its potential, study on this heat transfer process have not been as extensive as its single-phase counterpart. Particularly, to the best of our knowledge, no study on the boiling heat transfer in oval tube with different ellipticity. Thus, Numerical investigation using RPI wall boiling model and RNG k-Îµ turbulence model is conducted for different ellipticity of the oval tube. It is found that the heat transfer performance drop as the ellipticity increases with constant perimeter. Decrease of heat flux and increase of mass flow rate have positive impacts toward the heat transfer performance. The vapour generation resulting by the heat flux and mass flow rate is having high influence in the heat transfer coefficient and pressure drop. Â© The Electrochemical Society